O conceito de ‘crime grave’ e de ‘ato realizado no exercício das funções’ para atribuição de imunidades consulares: os limites às imunidades criminais de representantes consulares à luz do direito internacional comparado - Mariana Rodrigues Leite Ribeiro (2022)
This paper aims at identifying criteria to be evaluated when classifying a conduct as a 'grave crime' or as an ‘acts performed in the exercise of consular functions' for the purpose of removal or application of criminnal consular immunities established in articles 41 and 43 of the Vienna Convention of Consular Relations (VCCR), such as, personal inviolability against pretrial detention and immunity from criminal jurisdiction. For this purpose, a investigation based on Comparative International Law of predominantly jurisprudential nature will be carried out. Through the study of the decisions of domestic courts on the subject, it is intended to identify, describe and analyze parameters that allow the framing of consular conduct as 'grave crime' or ‘acts performed in the exercise of consular functions' for purposes of removal or application, in the criminal sphere, of the aforementioned immunities.